Deleterious heteroplasmic mitochondrial mutations are associated with an increased risk of overall and cancer-specific mortality - Hong, Yun Soo; Battle, Stephanie L.; Shi, Wen; Puiu, Daniela; Pillalamarri, Vamsee; Xie, Jiaqi; Pankratz, Nathan; Lake, Nicole J.; Lek, Monkol; Rotter, Jerome I.; Rich, Stephen S.; Kooperberg, Charles; et al. (Nature communications, 2023)
Mitochondria carry their own circular genome and disruption of the mitochondrial genome is associated with various aging-related diseases. Unlike the nuclear genome, mitochondrial DNA (mtDNA) can be present at 1000 s to 10,000 s copies in somatic cells and variants may exist in a state of heteroplasmy, where only a fraction of the DNA molecules harbors a particular variant. We quantify mtDNA heteroplasmy in 194,871 participants in the UK Biobank and find that heteroplasmy is associated with a 1.5-fold increased risk of all-cause mortality. Additionally, we functionally characterize mtDNA single nucleotide variants (SNVs) using a constraint-based score, mitochondrial local constraint score sum (MSS) and find it associated with all-cause mortality, and with the prevalence and incidence of cancer and cancer-related mortality, particularly leukemia. These results indicate that mitochondria may have a functional role in certain cancers, and mitochondrial heteroplasmic SNVs may serve as a prognostic marker for cancer, especially for leukemia. Mitochondrial DNA is known to exhibit heterogeneity of variants, even within a single cell. Here, the authors assessed this heteroplasmy of mitochondrial DNA within the UK Biobank cohort and showed that the presence of heteroplasmy and a functional score generated from heteroplasmic SNVs were associated with all-cause mortality and certain cancers.